Effectiveness of Integrated PowerPoint-iSpring Multimedia Prompting Questions on Learning Electrolyte and Nonelectrolyte Solutions Based on Guided Discovery Learning on the Learning Outcomes of Class X High School Students - Rani Mayresta; Guspatni Guspatni (Journal of Educational Sciences, 2022)
This study aims to reveal the level of effectiveness of the PowerPoint-iSpring multimedia integrated prompting questions on guided discovery learning based electrolyte and nonelectrolyte solution learning on the learning outcomes of class X SMA students. SDI Silungkang seen from the value of pretest and posttest . This type of research is pre-experimental with one group pretest posttest design . The population and sample in this study were class X SMA SDI Silungkang. The sampling technique in this study is a saturated sampling technique. The research instrument used was a multiple choice question with 20 items with 5 answer choices. From the results of the study, the average value of the pretest of students was 36.90 and the average value of the posttest was 84.52. Student learning outcomes showed that there were no students who scored below the KKM. The N-Gain value obtained is 0.76 in the high category. It can be concluded that the PowerPoint-iSpring multimedia integrated prompting questions in guided discovery learning -based electrolyte and nonelectrolyte solution learning is effective in improving the learning outcomes of class X students at SMA SDI Silungkang.